TIGAR Attenuates High Glucose-Induced Neuronal Apoptosis via an Autophagy Pathway - Zhou, Wenjuan; Yao, Yuan; Li, Jinxing; Wu, Dong; Zhao, Man; Yan, Zongting; Pang, Aimei; Kong, Liang (Frontiers in Molecular Neuroscience, 2019)
Hyperglycemia-induced neuronal apoptosis is one of the important reasons for diabetic neuropathy. Long time exposure to high glucose accelerates many aberrant glucose metabolic pathways and eventually leads to neuronal injury. However, the underlying mechanisms of metabolic alterations remain unknown. TP53 inducible glycolysis and apoptosis regulator (TIGAR) is an endogenous inhibitor of glycolysis and increases the flux of pentose phosphate pathway (PPP) by regulating glucose 6-phosphate dehydrogenase (G6PD). TIGAR is highly expressed in neuron. But the role of TIGAR in hyperglycemia-induced neuronal injury is still unclear. In this study, we observed that TIGAR and G6PD are decreased in the hippocampus of streptozotocin-induced diabetic mice. Correspondingly, in cultured primary neurons and Neuro-2a cell line, stimulation with high glucose induced significant neuronal apoptosis and down-regulation of TIGAR expression. Overexpression of TIGAR reduced the number of TUNEL-positive neurons and prevented the activation of Caspase-3 in cultured neurons. Furthermore, enhancing the expression of TIGAR rescued high glucose-induced autophagy impairment and the decrease of G6PD. Nitric oxide synthase 1 (NOS1), a negative regulator of autophagy, is also inhibited by overexpression of TIGAR. Inhibition of autophagy abolished the protective effect of TIGAR in neuronal apoptosis in Neuro-2a. Importantly, overexpression of TIGAR in the hippocampus ameliorated STZ-induced cognitive impairment in mice. Therefore, our data demonstrated that TIGAR may play anti-apoptosis effect via up-regulation of autophagy in diabetic neuropathy.